Evaluation of genetic divergence among Borrelia burgdorferi isolates by use of OspA, fla, HSP60, and HSP70 gene probes. - Wallich, R (1992)
In order to assess the genetic variation of immunologically relevant structures among isolates of the Lyme disease spirochete, Borrelia burgdorferi, three chromosomal genes encoding flagellin (fla) and the heat shock proteins HSP60 and HSP70, as well as the plasmid gene encoding outer surface protein A (OspA), from 55 different European and North American strains obtained from ticks and mammal hosts have been investigated by restriction fragment length polymorphisms (RFLPs). RFLPs of fla and the HSP60 and HSP70 genes revealed two distinct banding patterns (A and B) for each of the three genes and allowed the definition of four genomic groups [AAA, BBB, BBA, and B(A/B)A] for the three chromosomal genes. On the other hand, RFLPs of the OspA gene revealed six distinct banding patterns (types I to VI) making up six independent genomic groups for the plasmid-encoded gene. Furthermore, we have sequenced the chromosomal HSP60 gene from B. burgdorferi ZS7 and the plasmid-encoded OspA gene from two strains, ZQ1 and 19857. Alignment of the deduced HSP60 amino acid sequence from B. burgdorferi ZS7 (genomic group AAA) to a previously published HSP60 sequence derived from strain ACA-1, which according to the proposed classification is in a different genomic group (BBA), revealed a sequence identity of > 99%. Similar alignments of the OspA sequence of strain ZQ1 to those of other isolates that were published previously revealed sequence identities of between 70 and 94% among strains of distinct OspA genomic groups. These data indicate the existence of a restricted number of species-specific subgroups and clearly show that genotypic variation is much more pronounced for the OspA gene than for fla and the HSP60 and HSP70 genes. A phylogenetic tree constructed on the basis of distance matrix analyses of 12 OspA sequences supports the proposed classification of genomic groups of B. burgdorferi.